The impact of a firm's payout policy on stock prices and shareholders' wealth in an inefficient market - Kai Nekat; Peter Nippel (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2007)
In inefficient stock markets payout policy may be directly relevant for stock prices, not only by way of announcement effects considered in signaling games. We show that paying out free cash flow, either as a dividend or via repurchasing shares, has in general a positive price impact and increases shareholders' wealth, if the existence of non-smart investors and limits of arbitrage leads to market inefficiency. Shareholders gain more from a share repurchases instead of paying a dividend as long as capital gains are not heavily discriminated by taxation in relation to dividends. The positive price effect of dividends can be enhanced if the firm implements a dividend reinvestment plan (DRIP).
Keywords: G14; G35; 650; Payout policy; Dividends; Share Repurchases; Inefficient Market; Price Pressure; Dividend Reinvestment Plans (DRIPs); Dividende; Aktienrückkauf; Börsenkurs; Aktionäre; Wertzuwachssteuer; Aktienmarkt; Unvollkommener Markt; Theorie